Numerical analysis of roll waves generation on non-Newtonian fluids flowing down an inclined plane - de Oliveira Ferreira, Fabiana [UNESP]; de Freitas Maciel, Geraldo [UNESP]; Fiorot, Guilherme Henrique; da Cunha, Evandro Fernandes [UNESP] (Trans Tech Publications, 2014)
This article aims to determine roll waves generation criteria for mudflow events. A representative system of equations to mudflows is reached through Cauchy's equations (mass and momentum conservation) with proper stress tensor (non-Newtonian fluid) in shallow water conditions. Linear stability analysis is then applied to the system and two roll waves generation criteria are found: one related to Froude number and another related to flow disturbance frequency. Numerical simulations for both Newtonian and non-Newtonian fluids were carried. Good agreement was observed between numerical results and theoretical criteria. © (2014) Trans Tech Publications, Switzerland.
Keywords: Mudflows; Non-Newtonian fluid; Risks; Roll waves